Crossing the Borders - Monkey Pox in an HIV-Positive Pakistani Man Travelling from the Kingdom of Saudi Arabia; A Case Report - Muhammad Tabish Ikram; Faisal Hassan; Muhammad Irfan; Faryal Miraj; Yasir Ali; Shah Fiaz (Gandhara University, 2023)
Monkeypox, now called Mpox, was previously endemic to central and western Africa; however, a recent outbreak of Mpox was noticed outside its traditional endemic regions. We report a case of Mpox in a 33-year-old HIV-positive gentleman, the fourth case in Pakistan and the first in Khyber Pakhtunkhwa (KP). Risk factors like age, gender, and unsafe and risky sexual behavior put this patient at risk of Mpox.